2018
DOI: 10.1123/tsp.2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

From the Lab to the Field: Effects of Self-Talk on Task Performance Under Distracting Conditions

Abstract: This study explored the effectiveness of self-talk strategies on task performance under conditions of external distraction in laboratory and field experiments. In the laboratory experiment, 28 sport science students (Mage 21.48±1.58 years) were tested on a computer game requiring attention and fine execution following a baseline assessment and a short self-talk training. In the field experiment, 28 female basketball players (Mage 20.96±4.51 years) were tested on free-throwing, following a baseline assessment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
2
18
3
Order By: Relevance
“…Whereas some studies explored athletes' selftalk via descriptive methods, the self-talk literature in sport has been dominated by studies exploring, through interventions, the effectiveness of self-talk strategies, due to its direct applied value (Galanis, Hatzigeorgiadis, Comoutos, Charachousi, & Sanchez, 2018). Hatzigeorgiadis, Zourbanos, et al (2014) first described strategic self-talk as the use of cue words aiming at facilitating learning and enhancing performance, through the activation of appropriate responses.…”
Section: Strategic Self-talkmentioning
confidence: 99%
“…Whereas some studies explored athletes' selftalk via descriptive methods, the self-talk literature in sport has been dominated by studies exploring, through interventions, the effectiveness of self-talk strategies, due to its direct applied value (Galanis, Hatzigeorgiadis, Comoutos, Charachousi, & Sanchez, 2018). Hatzigeorgiadis, Zourbanos, et al (2014) first described strategic self-talk as the use of cue words aiming at facilitating learning and enhancing performance, through the activation of appropriate responses.…”
Section: Strategic Self-talkmentioning
confidence: 99%
“…Even though attentional aspects were not assessed in this study, it can be speculated that strategic self-talk assisted performance of the experimental group through maintaining or enhancing attentional functions. Such speculation can be based on previous findings supporting the attentional effects of strategic self-talk (e.g., Galanis et al, 2018Galanis et al, , 2021. Thus, the study provides in field indications that the attentional effects of self-talk may be a viable mechanism explaining the facilitating effects of self-talk on performance.…”
Section: Discussionmentioning
confidence: 62%
“…The first interpretation is that self-talk can help diminishing the potential impact of exertion. Galanis et al (2018), in a similar study in the field with basketball players taking a free throw test, reported that self-talk could counter the impact of external distractions and increased percentage of successful free throws. The second interpretation is that self-talk can help enhancing the effectiveness of focused attention required, thus improving performance in fine tasks.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Importantly, this self-talk is not a constituent of an intervention, although it can be indirectly influenced by interventions such as cognitive–behavioral therapy or mindfulness-acceptance approaches. On the other hand, strategic self-talk is described as a process of mechanically verbalizing predetermined keywords and phrases to achieve performance-related outcomes (e.g., Galanis, Hatzigeorgiadis, Comoutos, Charachousi, & Sanchez, 2018). Ziegler (1987), in her classic study, even named these procedures self-cueing instead of self-talk.…”
Section: The Conceptual Approachmentioning
confidence: 99%